THE DECLINE OF BUFFALO POPULATION IN THE MODERNIZATION ERA OF RICE AGRICULTURE - Paly, Basir (Proceeding Buffalo International Conference, 2013)
This study aimed to describe the decline of buffalo population in the era of modernization of rice agriculture between 1975 and 1985, which was capital-intensive and technology. This period was characterized by mechanized tillage with tractors, the use of an-organic fertilizers, the application of poison contacts and herbicide. Research was carried out using a survey method involving 20 buffalo farmers as respondents. They were deeply interviewed using a quisioner prepared before hand. Farmers were invited to recall the events experienced during that period. The results showed that the declined rate of buffalo population was about 7.35% per year. Factors contributed to that decrease were selling (52.06%), slaughtering (22.67), mortality (19.33%), and theft (6.44%). The selling itself was caused by several such factors as needs (40.15%), tractor-substitution (20.00%), disease (10.25%), contact poison (11.23%), and lack of forage (8.27%). Similarly, slaughtering was affected by needs (67.64%), contact poison (17.21%) and diseases (15.15%), while mortality was mainly due to disease (72.56%) and contact poison (27.44%). In conclusion, the modernization era of rice agriculture in the year 1975-1985 has significantly reduced the population of buffalo and caused lack of motivation of buffalo farmers.